Evaluation of the Esthetic Properties of Developmental Defects of Enamel: A Spectrophotometric Clinical Study - Fabrizio Guerra; Marta Mazur; Denise Corridore; Debora Pasqualotto; Gianna Maria Nardi; Livia Ottolenghi (The Scientific World Journal)
Objectives. Detailed clinical quantification of optical properties of developmental defect of enamel is possible with spectrophotometric evaluation. Developmental defects of enamel (DDE) are daily encountered in clinical practice. DDE are an alteration in quality and quantity of the enamel, caused by disruption and/or damage to the enamel organ during amelogenesis. Methods. Several clinical indices have been developed to categorize enamel defects based on their nature, appearance, microscopic features, or cause. A sample of 39 permanent teeth presenting DDE on labial surface was examined using the DDE Modified Index and SpectroShade evaluation. The spectrophotometric approach quantifies L* (luminosity), a* (quantity of green-red), and b* (quantity of blue-yellow) of different DDE. Conclusions. SpectroShade evaluation of the optical properties of the enamel defect enhances clinical understanding of severity and extent of the defect and characterizes the enamel alteration in terms of color discrepancy and surface characterization.